The Peptide Paradox in Pharmacology of Obesity - Sanjay Kalra,; Amandeep Singh,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2025)
Peptide biology is a fascinating subject, and peptide pharmacology even more so. Peptides have multiple bodily functions, including their work as hormones and metabolic modulators. However, certain pharmacodynamic and kinetic properties of peptides used in obesity result in paradoxical outcomes. It is helpful for the treating clinician to be aware of these peptide paradoxes, which not only help in understanding the rationale of using these drugs but also help to explain their differences in clinical actions. Keywords: biological paradox, dual agonists, GIP receptor agonists, GLP receptor agonists, glucagon agonists, peptide biology, semaglutide, tirzepatide, triple agonists,